PENGARUH PELATIHAN DAN PENGEMBANGAN SERTA LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Ika Sari Tondang (Halu Oleo University, 2023)
Employee performance greatly determines the success and sustainability of a company. Many efforts have been made by the company to improve the performance of its employees such as providing training and development as well as providing a comfortable work environment for employees. The purpose of this study was to examine the effect of training and development and the work environment on employee performance. This research was conducted at PT. Nusantara Plantation III Asahan District, North Sumatra. The sample used in this study was 100 employees who were selected using the purposive sampling method with the consideration that only permanent employees were used as respondents in this study. Research data was collected through interviews using a questionnaire. The data obtained were then analyzed using SmartPLS 4.0 software. The results of the research show that training and development have a positive effect on employee performance. The training and development provided to employees can improve the ability of employees to work so that employees can be more effective and efficient at work. Furthermore, the work environment has a positive effect on employee performance. Employees who feel comfortable at work, supported by adequate facilities at work will be able to maximize their performance.